2020
DOI: 10.7554/elife.52882
|View full text |Cite
|
Sign up to set email alerts
|

From behavior to circuit modeling of light-seeking navigation in zebrafish larvae

Abstract: Bridging brain-scale circuit dynamics and organism-scale behavior is a central challenge in neuroscience. It requires the concurrent development of minimal behavioral and neural circuit models that can quantitatively capture basic sensorimotor operations. Here, we focus on light-seeking navigation in zebrafish larvae. Using a virtual reality assay, we first characterize how motor and visual stimulation sequences govern the selection of discrete swim-bout events that subserve the fish navigation in the presence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 56 publications
6
29
0
Order By: Relevance
“…Instead, we found that zebrafish larvae did modulate their turn angle as a function of the absolute light intensity ( Figure 4G). Consistent with the results of a recent study (47), we found that the turn angle tended to increase after down-gradient scoots ( Figure 4H). This observation is reminiscent of the increase in turn angle after leaving a virtual circle (43).…”
Section: Defining the Nature Of Taste-driven Responses In Adult Fliessupporting
confidence: 93%
See 2 more Smart Citations
“…Instead, we found that zebrafish larvae did modulate their turn angle as a function of the absolute light intensity ( Figure 4G). Consistent with the results of a recent study (47), we found that the turn angle tended to increase after down-gradient scoots ( Figure 4H). This observation is reminiscent of the increase in turn angle after leaving a virtual circle (43).…”
Section: Defining the Nature Of Taste-driven Responses In Adult Fliessupporting
confidence: 93%
“…We show that zebrafish achieve positive phototaxis by increasing the amplitude of their turns when they are moving down-gradient and experiencing low light intensities. This new aspect of the sensorimotor strategy controlling zebrafish phototaxis has also been reported in an independent, recent study featuring closedloop light stimulations in a virtual-reality paradigm (47).…”
Section: Zebrafish Larvae Adapt Their Turn Amplitude To Stay Close Tosupporting
confidence: 64%
See 1 more Smart Citation
“…However, a comparison of the swimming statistics during the preadaptation period ( Figure 1C-D) and the test period ( Figure 1E-F) revealed that fish do not simply perform positive phototaxis, as has been suggested by previous studies [10,11,13,14] , but that they consistently turn towards the side closest in luminance to the preadaptation period. This indicates that larval zebrafish prefer a luminance similar to the preadaptation luminance, suggesting that this value serves as a set point for subsequent luminance-driven navigation.…”
Section: Larval Zebrafish Orient Towards a Set Point During Luminancesupporting
confidence: 67%
“…In this study, we establish luminance-based navigation in larval zebrafish as a model for investigating behavioral allostatic control. Previous work on luminance-based navigation in larval zebrafish has focused on their tendency to orient and swim towards brighter regions of luminance gradients; this behavior is termed positive phototaxis [10][11][12][13][14][15] . However, in naturalistic environments, luminance varies widely, both throughout the day and as fish move into and out of shade.…”
Section: Introductionmentioning
confidence: 99%